(untitled) (Journal of Educational Sciences, 2023)
The article analyzes the problems of improving the efficiency of teaching students in the humanities using digital educational technologies in the educational process and the use of mathematical tools. An analytical comparison was made of the models of the educational process of teaching humanities - traditional and using modern digital technologies, aimed at realizing the goals of standard curricula for schoolchildren. A modern approach to conducting research has become an analytical and factual presentation of the degree of influence of digital technologies on the dynamics of changes in the convective abilities of students using probabilistic-statistical methods. In accordance with the set goal and objectives, the result was obtained: mathematical confirmation of the dependence of changes in the progress of schoolchildren in teaching humanitarian disciplines on the quality and quantity of the use of modern digital technologies. The implementation of the tasks set is based on the use of statistical methods for processing time series information, by introducing an algorithm for determining empirical approximating functions from the class of monotone two-parameter functions. As a sample, data reflected on the Kundelik portal from grades 1 to 11 in all compulsory humanitarian disciplines and statistical data on the use of Bilimland digital educational resources were considered. Key words: statistical data, correlation, e-learning, time series, mathematical model.